INTERCONNECTION OF CONTRACTS: A STUDY ON THE SALE AND MAINTENANCE OF SACRIFICIAL COWS IN NAGARI SUMANI, SOLOK REGENCY (CASE STUDY OF MAK UJANG'S SACRIFICIAL COW MARKET) - Muhammad Latif Taftazani; Zainuddin Zainuddin (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
The aim of this research is to determine the form of buying and selling (bai), the form of ijarah, and the form of wadiah that occurs in the practice of buying and selling and caring for sacrificial cows carried out by the sacrificial cow seller "Mak Ujang," whose address is at Jorong Simpang AA, Nagari Sumani, X Koto Singkarak District, Solok Regency. The main problem in this research is why the seller is burdened with the obligation to care for the sacrificial cow after the sale and purchase until the time of slaughter. It also explores whether there are other contracts, such as ijarah and wadi'ah, accompanying the sale and purchase agreement (bai contract) in this case, and if so, whether it is justified to interconnect (combine three transactions simultaneously) in one contract. This research is field research with a qualitative approach. Data was collected using interview and documentation techniques. As a result of the research that has been carried out, the researchers found: 1) The form of buying and selling (bai) between the seller of the sacrificial cow, "Mak Ujang," and buyers who come from mosque/mushalla sacrificial committees and private community groups. 2) The form of wadi'ah (custody) of the sacrificial cow after the sale and purchase at the "Mak Ujang" sacrificial cow business until the day the sacrificial animal is slaughtered. 3) The form of ijarah in the transaction of caring for sacrificial cows after the sale and purchase at the "Mak Ujang" sacrificial cow business. From the discussion of the research findings, the researcher concluded that the interconnection of muamalah contracts in one transaction for buying and selling and caring for sacrificial cows—namely ba'i, ijarah, and wadi'ah—does not conflict with or violate Shari'a rules and is included in the 'uruf shahih' category. Therefore, it is justified according to the perspective of Islamic law.